Pattern of Cortical Changes in Sporadic Creutzfeldt-Jakob Disease - Tschampa, H.J.; Kallenberg, K.; Kretzschmar, H.A.; Meissner, B.; Knauth, M.; Urbach, H.; Zerr, I. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: High cortical signal intensity on diffusion-weighted (DW) or fluid-attenuated inversion recovery (FLAIR) images is increasingly described in sporadic Creutzfeldt-Jakob disease (sCJD). The aim of this study was to assess the extent and location of high cortical signal intensity, to investigate whether DW or FLAIR is superior in showing changes in cortical signal intensity, and to find out whether the distribution of the signal intensity changes is random or follows a common pattern.MATERIALS AND METHODS: We analyzed FLAIR and DW MR imaging scans of 39 patients with sCJD for hyperintense cortical signal intensity. We compared the sensitivity of the DW and FLAIR scans. We correlated the extent and location of the cortical signal intensity changes with concomitant changes in deep gray matter and the genotype of codon 129 of the prion protein gene.RESULTS: There was high signal intensity in the insula, the cingulate gyrus, and the superior frontal gyrus in 95%. The cortical areas near the midline also frequently showed the abnormal signal intensity (precuneus 87%, paracentral lobe 77%). The precentral and postcentral gyri were affected less frequently (41% and 28%, respectively). The DW MR imaging showed the cortical changes more effectively than FLAIR. There was no correlation between the distribution of changes and additional signal alterations in deep gray matter or the genotype of codon 129.CONCLUSION: The distribution of cortical signal intensity abnormalities in patients with sCJD follows a common pattern, affecting mainly the cortical areas near the midline, the insula, cingulum, and the superior frontal cortex. DW imaging is superior to FLAIR in the detection of cortical high signal intensity.